Effects of acupuncture combined with medication on patients with COVID-19 complicated with bipolar disorder: A protocol of systematic review and meta-analysis. Issue 45 (11th November 2022) - Huang, Wenjing; Zhu, Luwen; Wu, Minmin; Teng, Lili; Zhang, Mei; Song, Wenjing
Abstract : Background: There is growing evidence that coronavirus disease 2019 (COVID-19) can trigger acute episodes of mood disorders or psychotic symptoms. Reports on the treatment of COVID-19-related bipolar disorder (BD) are limited. Our study aimed to investigate the potential for new or recurrent BD due to COVID-19. We qualitatively evaluate clinical treatments (acupuncture combined with medication) and any potential pathophysiological links between infection and BD. Methods: We searched Embase, PubMed, Cochrane Library, Web of Science and MEDLINE (via Web of Science), Scopus, Chinese Biomedical Literature Database (CBM), Chinese National Knowledge Infrastructure Database, and the Wanfang Database from December 1, 2019, to September 15, 2022, to identify all articles on acupuncture combined with drugs used to treat COVID-19 complicated with bipolar disorders. Two researchers will screen the articles and extract the relevant information. Results: The results will provide a systematic overview of the current evidence on the use of acupuncture combined with drug therapy to treat COVID-19 complicated with bipolar disorder. Conclusion: The conclusions of this study will help clarify the effects of acupuncture combined with drug therapy on patients with COVID-19-related BD.